1995
DOI: 10.1002/aja.1002020106
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of retinoic acid receptor‐β isoforms during chick limb ontogeny

Abstract: Retinoids influence both morphogenetic events and differentiation during development of the vertebrate limb. These effects are mediated through nuclear retinoid receptors, which modulate target gene expression. We report here the cloning and characterization of three promoter-and splicing-variants of the retinoic acid receptor-P (RAR-P) from chick. These receptor isoforms are independently expressed during limb development. RARp2 but not RARPl transcripts are enriched three-fold in the posterior limb bud, refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 43 publications
(58 reference statements)
0
17
0
Order By: Relevance
“…Using this chicken-specific cDNA fragment as a probe, a 2771 bp cDNA coding for chicken Arnt was cloned from an incubation day 3.5 chick embryo cDNA library (11). This chicken Arnt clone coded for a protein of 806 amino acids, representing avian Arnt1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this chicken-specific cDNA fragment as a probe, a 2771 bp cDNA coding for chicken Arnt was cloned from an incubation day 3.5 chick embryo cDNA library (11). This chicken Arnt clone coded for a protein of 806 amino acids, representing avian Arnt1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the second PCR amplification a chicken-specific 584 bp cDNA fragment of Arnt was amplified using 200 nM Fp#1 and Rp#2 at 30 cycles of denaturation at 94°C for 30 s, annealing at 50°C for 1 min, and extension at 72°C for 30 s 4 mM MgCl 2 . The fragment was subcloned into pGemT (Promega), and used to screen an incubation day chick embryo cDNA library (11). Plaques were screened until clonal and sequenced using the T7 Sequenase kit, version 2 (Amersham Pharmacia Biotech, Piscataway, NJ).…”
Section: Methodsmentioning
confidence: 99%
“…Multiple isoforms of RARP have been described in the chick Smith et al, 1995) as well as in mammals, and several of these mammalian receptor mRNAs have been shown to be the subject of retinoid regulation (de ThB et al, 1989;Zelent et al, 1991;Nagpal et al, 1992). The sizes of the two RARP mRNAs (3.1 and 2.6 kb) in sympathetic ganglia in our studies are in agreement with previous reports for RARP mRNAs in whole chick embryo (Smith and Eichele, 1991) and chick face (Rowe et al, 1991a).…”
Section: Discussionmentioning
confidence: 99%
“…Receptors form dimers and act as ligand-dependent transcription factors binding to specific response elements (see Leid et al, 1992;Chambon, 1996 for reviews). These receptors show distinct patterns of expression in the developing mouse and chick, particularly in the limbs (Smith et al, 1995;Mendelsohn et al, 1992;Dollé et al, 1989Dollé et al, , 1994, and these structures are frequently found to be malformed in vitamin A teratogenesis or deficiency. More recently, the generation of transgenic mice (Cash et al, 1997;Lohnes et al, , 1994Lufkin et al, 1993;Yamaguchi et al, 1998) has identified more precisely the roles of these receptors and their agonists during embryonic development.…”
Section: Figmentioning
confidence: 99%